Life comparative analysis of energy consumption and CO₂ emissions of different building structural frame types. - Kim, Sangyong; Moon, Joon-Ho; Shin, Yoonseok; Kim, Gwang-Hee; Seo, Deok-Seok (Scientific World Journal, 2013)
The objective of this research is to quantitatively measure and compare the environmental load and construction cost of different structural frame types. Construction cost also accounts for the costs of CO₂ emissions of input materials. The choice of structural frame type is a major consideration in construction, as this element represents about 33% of total building construction costs. In this research, four constructed buildings were analyzed, with these having either reinforced concrete (RC) or steel (S) structures. An input-output framework analysis was used to measure energy consumption and CO₂ emissions of input materials for each structural frame type. In addition, the CO₂ emissions cost was measured using the trading price of CO₂ emissions on the International Commodity Exchange. This research revealed that both energy consumption and CO₂ emissions were, on average, 26% lower with the RC structure than with the S structure, and the construction costs (including the CO₂ emissions cost) of the RC structure were about 9.8% lower, compared to the S structure. This research provides insights through which the construction industry will be able to respond to the carbon market, which is expected to continue to grow in the future.